ПРИНЦИП ПРЕЕМСТВЕННОСТИ И ПРИМЕНЕНИЕ КОМПЬЮТЕРНОГО МОДЕЛИРОВАНИЯ СПЕКТРА ЩЕЛОЧНЫХ МЕТАЛЛОВ ПРИ ПРОВЕДЕНИИ РАЗЛИЧНЫХ УЧЕБНЫХ ЗАНЯТИЙ ПО АТОМНОЙ ФИЗИКЕ - Бабахова, Г.З. (SCIENCE and SOCIETY, 2025)
The article uses the principle of spectrum continuity of hydroxide metals and computer modeling in conducting various training sessions on atomic physics. Computer technology has been developed that allows for the formation of various spectral series of lithium and the separation of lines due to the spin-orbital interaction.
Keywords: atomic physics; quantum mechanics; spin; alkali metals; concept; electron